Henryana magnifica Yoshimoto (Hymenoptera: Eulophidae) in Brazil: New Records for the Amazon Rainforest and Brazilian Dry Forest - Fernandes, Daniell Rodrigo Rodrigues; Schoeninger, Karine; Lara, Rogéria Inês Rosa; Perioto, Nelson Wanderley (EntomoBrasilis, 2014)
Henryana magnifica Yoshimoto (Hymenoptera: Eulophidae) is reported for the first time in an Amazon rainforest area of Amazonas State and in a Brazilian Dry Forest area of Rio Grande do Norte State, Brazil. Henryana magnifica Yoshimoto (Hymenoptera: Eulophidae) no Brasil: Novos registros para a Floresta Amazônica e Caatinga Resumo. Henryana magnifica Yoshimoto (Hymenoptera: Eulophidae) é relatada pela primeira vez em uma área de Floresta Amazônica do Estado do Amazonas e em uma área de Caatinga no Rio Grande do Norte, Brasil.